The Exegetical Encounter between Jews and Christians in Late Antiquity - Grypeou, E. & H. Spurling (Leiden Brill, 2009)
This collection of essays examines exegetical encounters between Christians and Jews on the book of Genesis. Eminent scholars present outstanding studies on the subject of a ~Exegetical Encountera (TM) to illuminate the history of relations between Jews
Keywords: Bible. -- Genesis -- Criticism, interpretation, etc. -- Congresses. Bible. -- Old Testament -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600 -- Congresses. Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish -- Hi